Effectiveness of using liquid organic supplements (LOS) on the growth and survival of crayfish (Cherax quadricarinatus) - Saputra, Dedy Nurwan; AS, Agus Putra; Febri, Suri Purnama; Nazlia, Suraiya (Acta Aquatica: Aquatic Sciences Journal, 2025)
Aquaculture is an important sector in meeting global protein needs, where crayfish (Cherax quadricarinatus) has high economic potential. However, residual feed waste and degradation of the aquaculture environment often become major challenges, inhibiting growth and lowering the survival rate of crayfish. This study aims to analyze the effectiveness of using liquid organic supplements (LOS) in increasing the growth and survival of crayfish, as well as determining the optimal dose. The study used a completely randomized design (CRD) with four treatments and three replications with SOC doses of P1 = 0 ml/liter of water, P2 = 0.5 ml/liter of water, P3 = 1 ml/liter of water and P4 = 1.5 ml/liter of water. Parameters measured included absolute length growth, absolute weight, daily growth rate, and survival rate. The results showed that the provision of SOC had a significant effect on the growth of absolute length, absolute weight, and survival rate (P<0.05), but not significant on daily growth rate. The treatment with a dose of 1.5 ml/liter of water (P4) produced the best growth and survival performance, with an average absolute length growth of 1.3 cm, absolute weight of 0.58 grams, and a survival rate of 96%. The conclusion of this study is that SOC is effective for increasing the productivity of crayfish farming at a dose of 1.5 ml/liter of water. Keywords: Crayfish; Growth; Liquid Organic Supplement; Survival